2020
DOI: 10.1155/2020/1975904
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity Test of Extracts and Fractions of Cassava Leaves (Manihot esculenta Crantz) against Clinical Isolates of Staphylococcus epidermidis and Propionibacterium acnes Causing Acne

Abstract: This study is aimed at determining antibacterial activity from ethanol extracts and the most active fraction of cassava leaves against clinical isolates of Staphylococcus epidermidis and Propionibacterium acnes. Research carried out by the experimental method involved determination of plants, extraction with maceration method, fractionation with liquid-liquid extraction, antibacterial activity testing of extracts and fractions by agar diffusion method, determination of most active fraction from the extract, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 26 publications
0
18
0
11
Order By: Relevance
“…Water [ 20 , 21 ], ethanol [ 2 , 14 , 15 , 16 , 19 , 21 , 27 ], methanol [ 17 , 18 , 20 ], and other chemicals [ 13 ] have been considered as extraction solvents for plant ingredients. However, the antimicrobial activity of the plant extract against P. acnes not only depends on the extraction solvent, but also on various factors, such as the plant part, extraction time, and temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Water [ 20 , 21 ], ethanol [ 2 , 14 , 15 , 16 , 19 , 21 , 27 ], methanol [ 17 , 18 , 20 ], and other chemicals [ 13 ] have been considered as extraction solvents for plant ingredients. However, the antimicrobial activity of the plant extract against P. acnes not only depends on the extraction solvent, but also on various factors, such as the plant part, extraction time, and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…japonica M. 14 93.06 ± 0.64 47.04 ± 0.45 Lindera glauca S. and Z. 15 108.70 ± 0.33 27.50 ± 1.45 Lycoris radiata L'Her. 16 52.43 ± 0.45 12.62 ± 1.51 Oenothera laciniata N. 17 137.32 ± 0.35 33.47 ± 1.17 Chelidonium majus var.…”
Section: Total Phenolic and Flavonoid Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peptide was also found to limit the growth of S. aureus and S. epidermidis at 250 and 500 mg/L, respectively. Additionally, Mustarichie et al [36] revealed that the extract of cassava leaves exhibited antimicrobial activity against both C. acnes and S. epidermidis. The published data also indicate that non-antibiotic substances could reduce the numbers of C. acnes.…”
Section: Antimicrobial Activity Against the Anaerobic Strain Cutibactmentioning
confidence: 99%